Approximation of functions from the classes W_β^r H^α by Weierstrass integrals - Hrabova, U. Z.; Kalchuk, I. V.; Stepanyuk, T. A. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We investigate the asymptotic behavior of the least upper bounds of the approximations of functions from the classes W_β^r H^α by Weierstrass integrals in the uniform metric.